The Relationship Of Pregnant Women's Knowledge About Hypnobirthing With Pregnant Women's Attitude To Hypnobirthing Therapy Hana Kasih Clinic, Medan In 2020 - Arva Rochmawati Rochmawati; Dwi Ris Hasanah S (Science Midwifery, 2020)
Hypnosis methods that can be done starting during pregnancy can help reduce anxiety and fear levels. Hypnosis technique is one way that can be applied by pregnant women to gain peace when facing pregnancy and childbirth. The purpose of the study was to determine the relationship between knowledge of pregnant women about hypnobirthing and attitudes of pregnant women to hypnobirthing therapy at the Hana Kasih Clinic. This research method uses an observational-analytic design with a cross sectional approach, where the population is all pregnant women who perform pregnancy check-ups at the Hana Kasih Clinic with a total of 41 respondents. The sample size is 34 respondents through accidental sampling. The results of the analysis showed that knowledge of pregnant women about hypnobirthing did not affect the attitudes of pregnant women towards hypnobirthing therapy, where pregnant women who have less knowledge about hypnobirthing have a positive attitude towards hypnobirthing therapy. The results of the Chi-Square test obtained the value of =0.078 is greater than and thus Ho is accepted and Ha is rejected. It is recommended to health workers on duty at the Hana Kasih Clinic to provide pregnancy health counseling, especially about hypnobirthing, especially pregnant women who want to have a pain-free pregnancy.